Perancangan Sistem Pencatatan Akuntansi dan Pelaporan Keuangan pada CV. Nagoya City Fresh - Natalia, Felisha; Chandra, Budi; Ivone, Ivone (BUDGETING : Journal of Business, Management and Accounting, 2024)
Students participate in PKM in an MSME as part of a programme that encourages innovation. The goal of this PKM activity was to provide a hand to one of the MSMEs in creating a financial recording system that meets their needs so that it can be used for operational tasks. Nagoya City Fresh (CV) is our business partner for this project. The methodology used in this research is interviews and observations. The accounting recording system was designed using Microsoft Access. Based on the findings of the study and analysis carried out, it can be concluded that CV. Nagoya City Fresh uses a manual system for recording accounting information. Problems that arise on CV. Nagoya City Fresh is a lack of effectiveness and efficiency in preparing its financial reports, which has the potential to give rise to the spread of false information. The system produces various types of reports, including general ledger, trial balance, profit and loss report, financial situation report, and sales report. The implementation step has three distinct stages: first, familiarizing yourself with the characteristics of the system; second, sending and receiving systems developed by the author using Microsoft Access; and finally, obtain input from micro, small and medium enterprises (MSMEs). The system built has demonstrated effective functionality in offering improvements to accounting recording systems specifically designed for Micro, Small and Medium Enterprises (MSMEs). Keywords: Accounting Recording System, Financial Statement, Microsoft Access.